2002
DOI: 10.1115/1.1481355
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Fluid Flow Within an Anisotropic Porous Medium

Abstract: A numerical experiment at a pore scale using a full set of Navier-Stokes and energy equations has been conducted to simulate laminar fluid flow and heat transfer through an anisotropic porous medium. A collection of square rods placed in an infinite two-dimensional space has been proposed as a numerical model of microscopic porous structure. The degree of anisotropy was varied by changing the transverse center-to-center distance with the longitudinal center-to-center distance being fixed. Extensive calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 14 publications
6
84
0
Order By: Relevance
“…Aris [5], Koch and Brady [6], Han et al [7], and Vortmeyer [8]) were made to establish useful correlations for estimating the effective thermal conductivities due to thermal dispersion (See Kaviany [9]). Furthermore, Kuwahara et al [10] and Nakayama et al [11] conducted a series of numerical experiments by assuming a macroscopically uniform flow through a lattice of rods, so as to elucidate the effects of microscopic velocity and temperature fields on the thermal dispersion. It is also worthwhile to mention that Nakayama et al [12] derived a thermal dispersion heat flux transport equation from the volume averaged version of Navier-Stokes and energy equations and showed that it naturally reduces to an algebraic expression for the effective thermal conductivity based on a gradient-type diffusion hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Aris [5], Koch and Brady [6], Han et al [7], and Vortmeyer [8]) were made to establish useful correlations for estimating the effective thermal conductivities due to thermal dispersion (See Kaviany [9]). Furthermore, Kuwahara et al [10] and Nakayama et al [11] conducted a series of numerical experiments by assuming a macroscopically uniform flow through a lattice of rods, so as to elucidate the effects of microscopic velocity and temperature fields on the thermal dispersion. It is also worthwhile to mention that Nakayama et al [12] derived a thermal dispersion heat flux transport equation from the volume averaged version of Navier-Stokes and energy equations and showed that it naturally reduces to an algebraic expression for the effective thermal conductivity based on a gradient-type diffusion hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…By processing the results at the microscale, the effective hydrodynamic and thermodynamic parameters are computed as functions of the system properties (e.g., porosity, Reynolds number, flow direction, material properties). A drawback of the algorithm in [28,38,39] is, however, that it does not extend easily to porous media with very complex geometries (see for example Fig. 1.1), as building a "suitable" numerical grid of the flow domain is very difficult and time consuming.…”
Section: Spatially Periodic Geometriesmentioning
confidence: 99%
“…Also, the proposed transport model does not include a true thermal coupling between the fluid and the solids, i.e., conjugate heat transfer, and therefore does not support the effects of thermal material properties on the macroscopic thermodynamics. In this thesis we will follow a similar strategy for the computation of effective parameters as in references [28,38,39], however, we will extend it in two key areas. In Chap.…”
Section: Spatially Periodic Geometriesmentioning
confidence: 99%
See 2 more Smart Citations